Vicariance and oceanic barriers drive contemporary genetic structure of widespread mangrove species Sonneratia alba J. Sm in the Indo-West Pacific - Wee, Alison K. S.; Xian, Jessica Hui Teo; Chua, Jasher L.; Takayama, Koji; Asakawa, Takeshi; Meenakshisundaram, Sankararamasubramanian Halasya; Onrizal, -; Adjie, Bayu; Ardli, Erwin Riyanto; Sungkaew, Sarawood; Suleiman, Monica; Nguyen, Xuan Tung; et al. (MDPI, 2017)
Patterns of genetic structure are essential for a comprehensive understanding of the evolution and biogeography of a species. Here, we investigated the genetic patterns of one of the most widespread and abundant mangrove species in the Indo-West Pacific, Sonneratia alba J. Sm., in order to gain insights into the ecological and evolutionary drivers of genetic structure in mangroves. We employed 11 nuclear microsatellite loci and two chloroplast regions to genotyped 25 S. alba 483 2 of 21 populations. Our objectives were to (1) assess the level of genetic diversity and its geographic distribution; and (2) determine the genetic structure of the populations. Our results revealed significant genetic differentiation among populations. We detected a major genetic break between Indo-Malesia and Australasia, and further population subdivision within each oceanic region in these two major clusters. The phylogeographic patterns indicated a strong influence of vicariance, oceanic barriers and geographic distance on genetic structure. In addition, we found low genetic diversity and high genetic drift at range edge. This study advances the scope of mangrove biogeography by demonstrating a unique scenario whereby a widespread species has limited dispersal and high genetic divergence among populations.